Food insecurity status and its determinants among low-income households in Klang Valley, Malaysia - Azuddin, A. A.; Ramli, N. N.; Shamsudin, M. N.; Buda, M. (Universiti Putra Malaysia Press, 2024)
The present work aimed to determine the food insecurity status among low-income households in the Klang Valley, and identify the underlying factors contributing to it. The persistence of food insecurity within households, particularly among low-income families in Klang Valley, Malaysia, necessitates a closer examination of its determinants. Data were collected from 449 respondents representing low-income households, and these respondents were categorised into four groups based on the developed food insecurity status: food secure, mildly food insecure, moderately food insecure, and severely food insecure. A logistic regression model was employed to ascertain the influence of demographic factors, such as age, gender, race, education level, household income, and household size on food insecurity status. The results revealed that 46.33% of low-income households in Klang Valley were classified as mildly food insecure, 47.22% moderately food insecure, and 4.0% severely food insecure. The logistics regression analysis indicated that socio-demographic factors (race, education level, household income, and household size) significantly impacted food insecurity status of the low-income households. The findings suggested that financial and food assistance should be targeted to households with incomes below RM2,500 and larger family size. Insights from the present work would provide a basis for formulating strategies and policies aimed at alleviating food insecurity among low-income families in Klang Valley